2019
DOI: 10.33021/aegis.v3i2.711
|View full text |Cite
|
Sign up to set email alerts
|

Political Parties in Indonesia and the Internet: A comparative analysis

Abstract: <p>This is the first such study of the use of Internet by political parties in Indonesia. It also documents parties’ websites performance index and online popularity for campaigning in 2019. The purpose of this comparative study is to look at how the Internet was used by Indonesian political parties approaching the 2019 elections. Internet campaign consists of two parts: online presence through political party website, and political marketing through social media. Total of 16 parties participating the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It is especially urgent considering that Riau Province is recorded in 2018 to have the highest-by a far margin-land conflicts out of other provinces in Indonesia (Affandi et al, 2021;Handayani et al, 2019). Findings from the FGD echoed Rahman and Prihatini (2019) who stated that political parties and public bodies have not achieved their maximum potential in using digital media to disseminate information despite the fact that half of Indonesian national population using the Internet. These investigators similarly found that the quality of most political websites is subpar and have no relationship with financial resources.…”
Section: Discussionmentioning
confidence: 97%
“…It is especially urgent considering that Riau Province is recorded in 2018 to have the highest-by a far margin-land conflicts out of other provinces in Indonesia (Affandi et al, 2021;Handayani et al, 2019). Findings from the FGD echoed Rahman and Prihatini (2019) who stated that political parties and public bodies have not achieved their maximum potential in using digital media to disseminate information despite the fact that half of Indonesian national population using the Internet. These investigators similarly found that the quality of most political websites is subpar and have no relationship with financial resources.…”
Section: Discussionmentioning
confidence: 97%